An aural-performance analysis of revelation 1 and 11 - De Waal, Kayle B. (Studies in biblical literature, 2015)
Cover -- Contents -- Editor's Preface -- Preface -- Abbreviations -- Introduction and Procedure -- Chapter One: Literature Review and Methodology -- Introduction -- Literature Review -- Oral-Biblical Criticism and Oral Patterning -- Biblical Performance Criticism -- Sound Mapping -- Auditory NeuroScience -- The Auditory Process -- Methodology: An Aural-Performance Analysis -- Chapter Two: The Authorial Audience and the Culture in John's World -- Introduction -- A Brief Introduction to the Hearing Community in Revelation -- An Audience-Oriented Approach -- Audience Constructs -- The Informed Audience -- The Minimal Audience -- The Competent Audience -- Audience Markers -- The Communicative Environment: A Rhetorical Culture -- The Oral-Auricular Setting -- Reader Recognition -- Chapter Three: Ancient Performances and the Audience -- Introduction -- The Signficance of Oral Performance -- The Influence of Greek Drama -- Revelation's Liturgical Setting -- The Role of the Prophet-Performer -- The Role of Gesture -- Chapter Four: Aurality in the Ancient Literature -- Introduction -- The Importance of Hearing and Repetition -- Hearing the Gospel of Mark -- Hearing in Luke-Acts -- Hearing the Gospel of John -- Hearing Jewish Apocalyptic Literature -- The Apocalypse of Abraham -- Sound Map of "Apocalypse Abraham" 20 -- 2 Baruch -- Hearing the Book of Revelation -- Conclusion -- Chapter Five: An Aural-Performance Analysis of Revelation 1:1-21 -- Introduction -- Sound Map of Revelation 1:1-20 -- Performance Translation -- Word and Aural Analysis -- Aural-Performance Commentary -- To the Seven Churches -- Coming with the Clouds -- The Prophet-Performer, the Author, Authority and Character -- The Day of the Visions -- The "One like the Son of Man" -- The Resurrected One -- The Significance of Numbers -- Conclusion